The association of periodontal diseases and Sjogren’s syndrome: A systematic review and meta-analysis - Yang, Bo; Pang, Xuefei; Guan, Jiazhong; Liu, Xu; Li, Xiting; Wang, Yan; Chen, Zhuofan; Cheng, Bin (Frontiers in Medicine, 2023)
Background: The relationships between periodontal diseases and Sjogren’s syndrome were found inconsistent in current studies. Our objective is to clarify the relationship between periodontal diseases and Sjogren’s syndrome. Methods: A systematic review was performed and reported according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Electronic databases (EMBASE, PubMed, Web of Science, and Cochrane Library, from inceptions until November 24, 2021) were searched. The Newcastle-Ottawa Scale (NOS) and Agency for Healthcare Research and Quality (AHRQ) were applied for evaluating the quality of studies. Quality assessment of the certainty of evidence was performed based on the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) guidelines. When the output is the ratio, Odds ratio (OR) of periodontal diseases with Sjogren’s syndrome were calculated. When the output is the mean, weighted mean difference (WMD) of periodontal diseases with Sjogren’s syndrome were calculated. We conducted meta-analysis and estimated the pool sensitivity. Begg’s test was used to test the possibility of publication bias. We also carried out meta-regression and subgroup analysis to clarify the source of heterogeneity (I2>50%). Finally, we performed a trial sequential analysis (TSA) to identify the false positive or false negative outcomes that might occur during repeated updates. Results: 21 studies were included in this systematic review, with a total of 11435 subjects. Meta-analysis of 5 studies showed that there is a positive correlation between periodontitis and Sjogren's syndrome (OR = 2.12, 95% CI = 1.43–3.17; 5 studies, 6927 participants; low certainty of evidence). Meta-analysis of 16 studies showed that the periodontal condition of patients with Sjogren's syndrome was worse compared with the control group, and the scores of clinical periodontal parameters were relatively high. Conclusion: Sjogren’s syndrome patients seem to be more likely to be diagnosed with periodontal diseases. However, our results should be interpreted with caution considering the high heterogeneity.